Predictors of death including quality of positive pressure ventilation during newborn resuscitation and the relationship to outcome at seven days in a rural Tanzanian hospital - Moshiro, Robert (PLoS One, 2018)
BACKGROUND: Effective positive pressure ventilation (PPV) of non-breathing newborns is crucial in facilitating cardio-respiratory adaptation at birth. Identifying predictors of death in newborns receiving PPV is important in order to facilitate preventative strategies. OBJECTIVE: The objective of this study was to determine the perinatal predictors of death including the quality of PPV administered among admitted newborns. METHODS: An observational study of admitted newborns who received PPV after birth was conducted. Research assistants observed all deliveries and recorded perinatal events on data collection forms. Measured heart rate (HR) and ventilation parameters were then compared between newborns who died and survivors. RESULTS: Newborns (n = 232) were studied between October 2014 and November 2016. Newborns who died (n = 53) compared to survivors (n = 179) had more fetal heart rate (FHRT) abnormalities (12/53 vs 19/179; p = 0.03); lower initial HR (<100 beats/minute) at start of PPV (44/48 vs 77/139; p<0.001); and a longer time for HR to increase >100 beats/minute from birth (180 vs 149 seconds; p = 0.07). Newborns who died compared to survivors took longer time (14 vs 4 seconds; p = 0.008) and more inflations (7 vs 3; p = 0.006) to achieve an expired volume (V(t)) of 6 ml/kg, respectively. Median delivered V(t) during the first 60 seconds of PPV was less in newborns who died compared to survivors (5 vs 6 ml/kg; p = 0.12). Newborns who died proceeded to severe encephalopathy (15/31 vs 1/59; p<0.001) compared to survivors. CONCLUSION: Depressed newborns who proceeded to death compared to survivors, exhibited delayed HR response to PPV which may partly reflect FHRT abnormalities related to interruption of placental blood flow, and/or a timely delay in establishing adequate V(t). Depressed newborns progressed to moderate/severe encephalopathy. Improving FHRT monitoring to identify fetuses at risk for expedited delivery, coupled with optimizing delivery room PPV might decrease mortality in this setting.